1988
DOI: 10.1002/lipi.19880900803
|View full text |Cite
|
Sign up to set email alerts
|

DSC Studies Concerning Polymorphism of Saturated Monoacid Triglycerides in the Presence of Food Emulsifiers

Abstract: collected and converted to methyl esters using sodium methoxide. The methyl esters were identified by co-chromatography with reference compounds. Glycerol-1,3-dimyristate-2-laurate :Glycerol-1,3-dimyristate (0.02 g, 0.03 mmol) was reacted with lauryl chloride as described above to obtain, after t.1.c. separation, 0.03g of glycerol-l,3-dimyristate-2-laurate (010 yield: 92.0). Fatty acids present at the sn-2 position: O/O W/W 98.2 C12:o and 1.8 C14:o.Glycerol-l,3-dimyristate-2-palmitate : Glycerol-l,3-dimyristat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1991
1991
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…In tristearin, where melting and crystallization events are simultaneous and the temperature ranges over which the events occur are narrow (5-10°C wide at baseline), we obtain approximately 3-6 modulations at 2.5°C/min and 0.02 Hz which, is at the limit of acceptability. However, it is known that the α to β transformation occurs increasingly via a solid-solid route as the heating rate is decreased, thus bypassing the melt (24,25); thus, a different phenomenon may be observed at the very low heating rates.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In tristearin, where melting and crystallization events are simultaneous and the temperature ranges over which the events occur are narrow (5-10°C wide at baseline), we obtain approximately 3-6 modulations at 2.5°C/min and 0.02 Hz which, is at the limit of acceptability. However, it is known that the α to β transformation occurs increasingly via a solid-solid route as the heating rate is decreased, thus bypassing the melt (24,25); thus, a different phenomenon may be observed at the very low heating rates.…”
Section: Resultsmentioning
confidence: 99%
“…We have looked at the influence of operational parameters on MTDSC results and have attempted to interpret the results on the basis of what is known about tristearin polymorphism (1,8,(24)(25)(26)(27)(28).…”
mentioning
confidence: 99%
“…The α-form is probably stabilized by combined structures of tristearin and glyceryl monostearate on the intermolecular level. The ability of a partial glyceride to hinder another lipid transforming into its stable polymorph has been previously reported (31,32). In the chocolate industry, this specific effect is used to maintain an unstable polymorph of cocoa butter which appears more glossy than the recrystallised stable polymorph (33).…”
Section: Mixtures Of a Triglyceride And A Partial Glyceride And The Imentioning
confidence: 99%
“…Main mechanisms by which instability occurs in multiple emulsions of w/o/w type have been studied thoroughly and can be summarized to following possible mechanisms [77][78][79]. IV.…”
Section: Mechanisms Of Instabilitymentioning
confidence: 99%
“…Several reviews had been reported on the stabilization and mechanisms of drug release that concentrates on different mechanism and methods of stabilization [77][78][79]. A number of approaches had been tried out to improve the stability of multiple emulsion and many have been suggested for further investigations.…”
Section: Stabilization Of Multiple Emulsionmentioning
confidence: 99%